Metode Learning Management System (LMS) Idu Untuk Mendukung Kegiatan Belajar Mengajar MIT Pada Perguruan Tinggi Raharja - Untung Rahardja; Qurotul Aini; Siti Ria Zuliana (CICES (Cyberpreneurship Innovative and Creative Exact and Social Science), 2016)
Currently the entire field has been supported by technology, especially the world of education in the learning process to determine the quality of a college graduate. In the world of education Perguruan Tinggi Raharja has implemented iLearning learning methods to achieve the learning objectives. Graduate students are given learning experiences using methods iLearning the learning process using the media Ten Pillar IT iLearning (TPi). But the learning process is not running properly and still undeniably versatile use paper as a method of learning in general, Therefore at this time to achieve the learning objectives very effectively implement methods Learning Management System (LMS) iDu which can be accessed online anytime and anywhere easily. The purpose of this study to determine measure the success of the learning process at MIT class that still use manual systems in the learning process . This study uses a quantitative approach with descriptive correlational survey method . Sample collection techniques in this study was based on the results of the student survey MIT classes . Data collector by using questionnaires and documentation . Results from the study showed that the better level the results of the learning process to use iDu’s system where students could complete the learning easily anywhere and anytime . In this journal Identified there are three (3) the problems faced and the solutions given are by utilizing campus Learning Management System (LSM) iDu. Do 8 (eight) literature review as a post-graduate study materials. And there were 13 (thirteen) advantages and 1 (one) shortcomings of this study. The implementation is done in the course MasteringInformation Technology (MIT). This study is expected to improve the quality of graduates from graduate students in Perguruan Tinggi Raharja.